Integration of R&D and new product development: case studies of Brazilian high-tech firms - Jugend, Daniel [UNESP]; Silva, Sérgio Luis da (Inderscience Publishers, 2014)
One of the aspects that influence good performance of new product development (NPD) at high-tech companies is the integration of research and development (R&D) and the other functions involved with NPD. The objective of this paper is to examine why Brazilian medium and large sized high-tech companies are different with respect to the integration of R&D with NPD. An analysis of case studies was conducted at five Brazilian high-tech firms. Among the results, collectivism, which is characteristic of the Brazilian organisational culture, was seen to manifest itself in companies through the adoption of cross-functional teams; the valorisation of personal relations, which is stimulated by physical proximity; and project managers’ ample participation in different functions involving NPD.
Keywords: Innovation; Integration; New product development; NPD; High-tech firms